Authority and imitation : a study of the Cosmographia of Bernard Silvestris - Kauntze, Mark (Mittellateinische Studien und Texte, 2014)
In Authority and Imitation Mark Kauntze presents a new reading of the twelfth-century Cosmographia of Bernard Silvestris, showing how this allegory of creation adapted ancient authorities to contemporary debates about natural philosophy.